Sense I had nothing to do I thougt I do some math but I seem to have forgot derivative...

"Determen dy/dx in (1,2) for 4xy^2 - 12xy + 13 = 5x"

4 d/dx (xy^2) - 12 d/dx(xy) + d/dx(13) = d/dx(5x)

4(d/dx(x) + x d/dx(y^2)) - 12(d/dx(x) + x (d/dx(y)) + d/dx(13) = d/dx(5x)

4(d/dx(x) + x d/dy(y^2) dy/dx) - 12(d/dx(x) + x (d/dy(y) dy/dx) + d/dx(13) = d/dx(5x)

4(1 + x*2y^(2-1) dy/dx) - 12(1 + x*1 dy/dx) + 0 = 5

4+4x2y dy/dx - 12-12x dy/dx = 5

dy/dx + dy/dx = (5-4+12)/(4x2y-12x)

2 dy/dx = 13/4 <- This is the right awnser

dy/dx = 13/8 <- This is wrong

Anyone that can explain for a dumb kid what he is doing wrong?

"Determen dy/dx in (1,2) for 4xy^2 - 12xy + 13 = 5x"

4 d/dx (xy^2) - 12 d/dx(xy) + d/dx(13) = d/dx(5x)

4(d/dx(x) + x d/dx(y^2)) - 12(d/dx(x) + x (d/dx(y)) + d/dx(13) = d/dx(5x)

4(d/dx(x) + x d/dy(y^2) dy/dx) - 12(d/dx(x) + x (d/dy(y) dy/dx) + d/dx(13) = d/dx(5x)

4(1 + x*2y^(2-1) dy/dx) - 12(1 + x*1 dy/dx) + 0 = 5

4+4x2y dy/dx - 12-12x dy/dx = 5

dy/dx + dy/dx = (5-4+12)/(4x2y-12x)

2 dy/dx = 13/4 <- This is the right awnser

dy/dx = 13/8 <- This is wrong

Anyone that can explain for a dumb kid what he is doing wrong?